Jejak Sejarah dan Makna Budaya : Analisis Toponimi Penamaan Desa Wilamaci dan Tolotangga di Bima - Arfah Arfah; Aswandikari Aswandikari; Burhanuddin Burhanuddin; Saharudin Saharudin; Sirulhaq Sirulhaq (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Toponymy or the study of historical traces and cultural meanings of Wilamaci Village and Tolotangga Village in Monta District, Bima Regency. One of the fundamental elements in the construction of a special identity and culture of a society. More than just a geographical label on a map, each toponym contains a collective narrative, traces of civilization, and a reflection of the worldview of the community that named it, and functions as a linguistic artifact that not only marks a physical location, but also stores a wealth of historical information passed down from generation to generation. The objectives of this study are: 1) to analyze the linguistic origins and lexical meanings of the names of Wilamaci Village and Tolotangga Village; 2) to reveal historical traces, including important events, influential figures, or migration dynamics reflected in their names; and 3) to analyze the cultural meanings contained therein, including community values, belief systems, and local folklore. This study uses an ethnolinguistic approach with a qualitative descriptive method through long-distance interviews and document studies. The research results show that both toponyms are rooted in local terms describing past natural conditions and social activities. Furthermore, the names Wilamaci and Tolotangga represent traces of early migration groups and cultural symbols still maintained by the Bima people today. These findings enrich the study of toponymy and anthropolinguistics and contribute to the preservation of regional cultural identity.